Edge plasma measurements on the OP 1.2a divertor plasmas at W7-X using the combined probe. (May 2019) - Drews, P.; Killer, C.; Cosfeld, J.; Knieps, A.; Brezinsek, S.; Jakubowski, M.; Brandt, C.; Bozhenkov, S.; Dinklage, A.; Cai, J.; Endler, M.; Hammond, K.; et al.
Highlights: The measurements with a reciprocating Langmuir probe have been carried out in the divertor plasmas at Wendelstein 7-X. The measurements yielded electron temperatures and densities The effect of the toroidal current evolution on the magnetic topology and the edge profiles was studied. Finally the measurements were compared to the EMC3-EIRENE modelling. Abstract: During its second operational campaign (OP 1.2a) W7-X operated with an edge island divertor. Much higher densities ( 10 20 m − 3 ) than in to the previous, limiter campaign were achieved. In order to asses this improved performance and the nature of transport with regard to the expected higher densities and other parameters such as the electron and ion temperature, the electric field and plasma flow, measurements at the plasma edge were conducted with reciprocating probe, mounted on a Manipulator. The probe contains a set of Langmuir pins, Mach probes, compensation coils and a set of 3D pick up coils for the measurement of the local magnetic field and fluctuations, and an ion sensitive probe. It has been observed, in addition to differences due to the magnetic configurations, that the magnetic topology is sensitive to the plasma conditions, especially to changes due to a evolving toroidal plasma current. Measurements from divertor cameras showed that an increasing toroidal current in the standard configuration broadened the heat flux and shifted the strike line considerably. These down-stream observation can be complemented with the measurements at the mid-plane with the manipulator mounted probes. During the experiments the edge island remnant was identified with the measured edge plasma profiles and compared with the predictions from the field line tracing code. Those electron densities and temperatures have been used as an input for understanding edge transport with the EMC3-EIRENE modeling. The results from EMC3-EIRENE also help improve the caculated density profiles, since the modelling provides a profile of the effective charge Z eff .